Improving Student Learning Outcomes in Islamic Education Learning Using Wordwall Media in Senior High Schools - Firdaus, Fadhilah (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using wordwall media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data of this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics. The results of the study indicate that wordwall media can improve student learning outcomes in Islamic religious education learning. Thus, the use of wordwall media can be used as an alternative to improve student learning outcomes in Islamic religious education learning.